Why Do Individuals Engage in Phubbing? An Empirical Study Integrating Fear of Missing Out, Boredom Proneness, Smartphone Use - Dr. Komal Nagar, Nitin Gupta, (European Economic Letters (EEL), 2024)
Increased use of smartphones has necessitated research into its negative psychological and physiological effects on individuals. This study seeks to examine the relationship between psychosocial factors-boredom proneness, fear of missing out (FoMO) and life satisfaction with phubbing. The research also investigates the mediating effect of Phubbing on FoMO, boredom proneness and life satisfaction. Design/Methodology/Approach- A conceptual model is proposed and validated by extending research on smartphone use. A survey of 350 respondents was conducted using purposive sampling technique to empirically test the hypothesized linkages among the constructs using structural equation modeling. Findings- Results of the study confirmed that individuals who engage in phubbing behavior exhibit traits of boredom and FoMO. Findings also reveal that phubbing has a positive effect on life satisfaction. Additionally, results confirm that phubbing mediates the association between FoMO and life satisfaction. Limitations- The sample consisted of only students enrolled at a large, public university in India. While research suggests that students are the largest users of smartphones, and that smartphones are an important aspect of this generation’s culture and identity, our ability to generalize these results to other populations is limited and therefore replicating this study among different demographic and geographic regions will aid in generalizing the findings of the present study. Practical Implications- Findings of this study enrich the literature on smartphone use and reveals that phubbing is a direct consequence of individuals’ desire to gratify social and psychological needs. Outcome of the study also benefit practitioners by allowing them to understand and develop new interventions aimed at the youth so that they can be protected against the negative effects of smartphone use. Originality/Value- The present study attempts to analyze the effect of FoMO and boredom proneness on phubbing. Understanding the predictors of phubbing is important, considering the negative effects of this behavior on life satisfaction. This study makes significant contributions to the existing body of knowledge about how increased fear of missing out, boredom proneness and phubbing may affect overall life satisfaction.